Designer Nanomaterials through Programmable Assembly. Issue 3 (28th September 2021) - Kahn, Jason S.; Gang, Oleg
Abstract: Nanoparticles have long been recognized for their unique properties, leading to exciting potential applications across optics, electronics, magnetism, and catalysis. These specific functions often require a designed organization of particles, which includes the type of order as well as placement and relative orientation of particles of the same or different kinds. DNA nanotechnology offers the ability to introduce highly addressable bonds, tailor particle interactions, and control the geometry of bindings motifs. Here, we discuss how developments in structural DNA nanotechnology have enabled greater control over 1D, 2D, and 3D particle organizations through programmable assembly. This Review focuses on how the use of DNA binding between nanocomponents and DNA structural motifs has progressively allowed the rational formation of prescribed particle organizations. We offer insight into how DNA‐based motifs and elements can be further developed to control particle organizations and how particles and DNA can be integrated into nanoscale building blocks, so‐called "material voxels", to realize designer nanomaterials with desired functions. Abstract : This Review discusses progress on principles and methods for creating nanoparticle‐based materials via programmable self‐assembly. We review the pathways by which DNA‐based assembly has been used to impart organization to prescribed particles. DNA, as a programmable structural element, can be used to create designer nanomaterials from inorganic and organic nanoparticles of multiple types and functionalities.